EFEK MULTI STRAIN PROBIOTIK TERHADAP KADAR LDL-C Rattus norvegicus HIPERLIPIDEMIA - Kadeq Novita Prajawanti; Jusak Nugraha; Harianto Notopuro; Amellya Octifani; Yohanes Adrian Kapri Negara (Jurnal Media Analis Kesehatan, 2023)
Hyperlipidemia is an increase in one or more plasma lipids and the main cause is related to the pattern of food intake. Among the many intestinal microbes, Lactobacillus, Bifidobacterium have been shown to affect the host beneficially by improving the intestinal microbial balance and are therefore categorized as probiotics. The aim of this study was to determine the effect of multi-strain probiotics Lactobacillus rhamnosus and Bifidobacterium bifidum on reducing LDL-C in rat fed HFD 1% per body weight. This True Experimental Research with Pretest-Posttest Design used Rattus norvegicus which was divided into 5 groups each K- (standard feed + tap water), K+ (HFD without probiotics), P1 (HFD + 2mL probiotics), P2 (HFD + 2 .5mL probiotics) and P3 (HFD + 3mL probiotics). The results of the LSD test for LDL cholesterol levels after administration of probiotics, the group that had a significantly different value was in the K- to K+ group with p=0.00; K+ to P1, P2 and P3 with p 0.00 each. Meanwhile, among the treatment groups that were given probiotics, only the P2 to P3 groups showed a significant difference with a p value = 0.037.